Innovations in the banking sector in Ukraine - Roshylo, Violetta (Skhid, 2016)
This paper covers the features of applying innovations in the banking sector in Ukraine. It was found that for building customers' confidence and meeting their needs, banks shall continually improve the quality of services aided by active introduction of innovations. In order to clarify the peculiarities of innovation in the banking sector, the basic concepts of innovations and innovative activity were defined. The significance of globalization for the domestic banking system is determined. The list of positive effects of globalization on the application of innovation in banks is provided. The role of the innovative capacity of banks to implement innovation is characterized. The model of structured approach to innovative activity of a bank is built, which consists of resources required for introducing innovations, effect of external factors and factors of innovative activity of a bank. The components of an integrated approach to management of banking innovative activity are given. Classification of bank innovations is provided and the life cycle of innovative product is described, which includes three phases, namely growth, maturity and decline. The most current innovations being introduced by the banks are identified, such as mobile banking and Internet banking. The essence of mobile banking is described, which includes SMS informing about the operation on the account, the function of inquiry of the account balance, etc. Internet banking is separately described, which is being actively implemented by the banks in Ukraine in their practice of banking services. Classification of Internet banking services is provided, including basic services and optional services. The importance of such information innovations as applications for smartphones is outlined. It was established that innovations in the management system of banks in Ukraine take one of the leading roles and ensure their sustainable development. Through innovations financial institutions of Ukraine can capture positive and new trends not only in the domestic market of banking services but also go beyond it.